Pendidikan Multikultural Di Indonesia Berbasis Akhlak Tasawuf - Rahmat Lutfi Guefara (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
This research aims to describe how the moral attitudes taught in the science of Sufism can serve as a foundation for multicultural education. The research method used is qualitative phenomenology, with an approach that includes in-depth interviews, direct field observations, and general observation. The result of this research is a design for multicultural education based on Sufi ethics. This study explores the collaboration between the concept of multicultural education and Sufi behavior in Sufism teachings. Both elements have developed significantly and have influenced various aspects of life. However, this research offers an integration of these two elements into a Sufi-oriented multicultural education system. This new model is expected to create serenity and peace for the Indonesian nation.